ANALISIS SISTEM AKUNTANSI PENJUALAN TUNAI DALAM MENINGKATKAN EFEKTIVITAS PENGENDALIAN INTERNAL PADA PT USAHA UTAMA BERSAUDARA - Arlin Choirun Nisa; Oryza Tannar (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The purpose of this research is to assess and test the Cash Sales Accounting System implemented by PT Usaha Utama Bersaudara in order to increase the effectiveness of internal control. By directly interviewing the parties involved, this research collected primary data using a descriptive qualitative research approach. Apart from interviews, the author also carried out documentation and literature studies to assist the research process. Based on this research, PT Usaha Utama Bersaudara has implemented a fairly good Cash Sales Accounting System. However, there are still several problems that need to be overcome, such as separating duties between the shipping function and the warehouse function so as to minimize the risk of errors in sending or recording goods. Apart from that, the internal control carried out at PT Usaha Utama Bersaudara is also quite good with the separation of duties, clear authorization and implementation of healthy practices. However, it is best to make cash deposits to the bank on the same day.